2007
DOI: 10.1089/acm.2007.0567
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Glutathione and Total Antioxidant Status with Yoga

Abstract: Regular practice of yoga can maintain or improve antioxidant level of the body. The clinical relevance is that yoga practice can be used to maintain the antioxidant defense system under stressful conditions of training as observed in the case of soldiers and athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 28 publications
3
38
0
Order By: Relevance
“…Previous researcher showed that yoga has the beneficial role to improve cognition and BDNF levels (Xiong, andDoraiswamy 2009, Naveen et al 2013). Yogic practices also have potentially beneficial effects on lipid profiles and lower oxidative stress, both of which could in turn reduce the risk for cerebrovascular disease-and age-related neurodegeneration (Singh et al 2008;Sinha et al 2007). Further, meditation may potentially strengthen neuronal circuits and enhance cognitive performance (Froeliger et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous researcher showed that yoga has the beneficial role to improve cognition and BDNF levels (Xiong, andDoraiswamy 2009, Naveen et al 2013). Yogic practices also have potentially beneficial effects on lipid profiles and lower oxidative stress, both of which could in turn reduce the risk for cerebrovascular disease-and age-related neurodegeneration (Singh et al 2008;Sinha et al 2007). Further, meditation may potentially strengthen neuronal circuits and enhance cognitive performance (Froeliger et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Specific exercise can be performed with electronic devices at home or gym, which is costly. Furthermore, studies comparing the effects of yoga and exercise seem to indicate that, in both healthy and disease population, yoga may be as effective or better than exercise at improving a variety of health-related outcome measures such as heart rate variability (HRV; Bowman et al 1997), cognitive performance (Gothe et al 2013), blood glucose (Gordon et al 2008;Singh et al 2008), blood lipids (Singh et al 2008), salivary cortisol (Smith et al 2011), and oxidative stress (Sinha et al 2007). Except all these, yoga is helpful for improving subjective measures of fatigue (Oken et al 2004(Oken et al , 2006, pain, and sleep in healthy and ill population (Yurkuran et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, previous studies showed evidence of the beneficial properties of yoga in treating various diseases, including cardiovascular disorders, various types of cancers, back pain, and immune dysfunctions, as well as psychological disorders, such as anxiety or depression. [7][8][9][10] Regarding the physiologic condition, yoga practice not only can improve muscular efficiency, endurance time, and enhancement of aerobic exercise capacities but also can reduce perception of exhaustion after exertion caused by physical exercise. 11,12 In addition, yoga is widely used to alleviate mental stress via modulation of hypothalamuspituitary-adrenal axis activation.…”
Section: Introductionmentioning
confidence: 99%
“…Control of several risk factors like hypertension, type II DM lipids [4][5][6][7][8][9][10]. Reversal or preventive effects of both psychosocial and oxidative stress and reduction of inflammation [18][19][20][21] may be contributing factors. Further studies are needed to delineate the exact mechanisms.…”
Section: Discussionmentioning
confidence: 99%